Modos de vida e de trabalho das mulheres que zungam em Luanda - Monteiro, Indira Lazarine Catoto (2012)
This dissertation analysis the modes of living and of working of the zungueira woman or street vendor in Luanda, capital of Angola. Since period before the independence (1975), the country lives situations of extreme poverty and socioeconomic precariousness, that manifests by informal work activities and so much precarious street trading situated in the limits of the violation of rights. Angola has passed by a long armed conflict (1975-2002), with agglomeration of populations displaced by the war in the cities, making greater the social question and the resettlement of part of this population that is interested in return (2002) to your origin areas. This situation has worsened still more the social condition of the population in situation of poverty, making bigger the socioeconomic inequality, the insufficiency in the public policies, the precarious access to the basic social services as water, health, habitation, education and citizen participation. This process has triggered the development of survival strategies and made greater the number of people that have done the informal work, with expressive presence of the zungueira woman. This study wants to know and analyze the reality of this woman and provide visibility of the situation of extreme precariousness, like subsidy for the elaboration of public policies directed to the improvement of your conditions of life. By the realized interviews with zungueira women that resides in suburban neighborhoods of Luanda, the qualitative research analyzed the daily practices of those women in your link with the zunga, while the necessary survival strategy to the creation of life conditions and the significance of the street trading in your lives